Quadratic-Phase Hankel Transformation and Calderón’s Reproducing Formula - Roy, Chandra; Kumar, Tanuj; Prasad, Akhilesh; Jha, Govind Kumar (Communications in Mathematics and Applications, 2024)
In this paper, we have explored fundamental properties of the quadratic-phase Hankel transformation. Additionally, we have derived Calderón’s reproducing formula for quadratic-phase Hankel convolution based on the theory of the quadratic-phase Hankel transformation.
Keywords: Hankel transformation; Quadratic-phase Hankel transformation; convolution; Calderón’s formula